Prevalence of thrombophilia according to age at the first manifestation of venous thromboembolism: results from the MAISTHRO registry. (8th October 2013) - Weingarz, Lea; Schwonberg, Jan; Schindewolf, Marc; Hecking, Carola; Wolf, Zsuzsanna; Erbe, Matthias; Weber, Adele; Lindhoff‐Last, Edelgard; Linnemann, Birgit
Summary Thrombophilia is a well‐established risk factor for a venous thromboembolic event (VTE), and it has been proposed that hereditary thrombophilia may substantially contribute to the development of VTE in young patients. We aimed to analyse the prevalence of thrombophilia with special regard to the age of VTE manifestation. The study cohort consisted of 1490 patients (58% females) with a median age 43 years at the time of their first VTE. At least one thrombophilic disorder was identified in 50·1% of patients. The probability of detecting a hereditary thrombophilia declined significantly with advancing age (from 49·3% in patients aged 20 years and younger to 21·9% in patients over the age of 70 years; P < 0·001). This may be primarily attributed to the decreasing frequencies of the F5 R506Q (factor V Leiden) mutation and deficiencies of protein C or protein S with older age at the time of the initial VTE event. Moreover, thrombophilia was more prevalent in unprovoked compared with risk‐associated VTE (57·7% vs. 47·7%; P = 0·001). The decline in the prevalence of hereditary thrombophilia with older ages supports the use of a selected thrombophilia screening strategy dependent on age and the presence or absence of additional VTE risk factors.